Maimonides medical aphorisms : Hebrew translation by Zeraḥyah ben Isaac ben Sheʼaltiel Ḥen - Maimonides, Moses, 1135-1204 (Maimonides, Moses, 1135-1204. Medical works of Moses Maimonides, 2020)
"The original Arabic text of Maimonides' major medical work, Medical Aphorisms, was critically edited and translated into English by Gerrit Bos in the years 2004-2017, and published in earlier volumes of the book series The Medical Works of Moses Maimonides. The present work is the first critical edition of the medieval Hebrew translation by R. Zeraḥyah ben Isaac ben Sheʼaltiel Ḥen. Zeraḥyah, active as a translator in Rome from 1277 to 1291. He was not only known for his translations of Maimonides' medical works, but also for his translations of medical works by Galen and Ibn Sīnā, and for his philosophical works by Aristotle and Averroes. Zeraḥyah's unique Hebrew translation adheres closely to Maimonides' Arabic text and contains many Italian and Latin loanwords"--